2015
DOI: 10.1177/0020872815594222
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the help-seeking decisions of sexual assault survivors: Implications for social work practice in Hong Kong

Abstract: The study aims to adopt a social constructionist and feminist approach to explore the interactional factors that influence the decision of sexual violence survivors to seek help and disclose their sexual abuse experiences in Hong Kong. The study has adopted both quantitative and qualitative research methods. Results suggest that the decisions of sexual assault survivors to disclose their experiences or seek help are not characterized by a rational process based on thoughtful calculation or cost-benefit analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…The next step for social workers is to equip themselves with relevant knowledge and skills. Social workers can help sexually exploited adolescents to redefine their experiences, and they can also encourage survivors to break their silence to eliminate isolation (Mennen, 1990) and the self-blame and internalisation of negative self-evaluation (Leung, 2015). The police can contribute to facilitating reporting and detecting child and adolescent sexual exploitation and/or abuse cases.…”
Section: Implications For Social Workmentioning
confidence: 99%
“…The next step for social workers is to equip themselves with relevant knowledge and skills. Social workers can help sexually exploited adolescents to redefine their experiences, and they can also encourage survivors to break their silence to eliminate isolation (Mennen, 1990) and the self-blame and internalisation of negative self-evaluation (Leung, 2015). The police can contribute to facilitating reporting and detecting child and adolescent sexual exploitation and/or abuse cases.…”
Section: Implications For Social Workmentioning
confidence: 99%
“…They suggested either a discursive misstep on the part of a supporter or survivor/victim isolation could be catastrophic. Chinese participants discussed dangers associated with exposure of victim status, including compromised marriageability ( Leung, 2017 ), criminalization, and mental health disruption.…”
Section: Resultsmentioning
confidence: 99%
“…In China, digital storytelling for sexual violence victims is important since other self-expression channels, such as hotlines, assistance from social workers and news media coverage, are largely insufficient. Studies have demonstrated that help-seeking decisions of sexual assault victims were shaped by interpersonal interactions and the availability of support rather than by rational processes based on thoughtful calculations or cost-benefit analysis (Leung, 2017). China does not have social welfare protection and social support for sexual harassment and sexual assaults.…”
Section: Identity As Self-presentation: Difficulties In Naming Sexual Harassment Through Sharing Personal Experiencesmentioning
confidence: 99%